Avoiding deadlock and reducing starvation and blocking in automated manufacturing systems. - Wu, N. (IEEE Transactions on robotics and automation)
Deadlock-free operations of automated manufacturing systems (AMS) are essential for high machine utilization and productivity. Based on the resource-oriented Petri net models of AMS and our previous work (2000) on a necessary and sufficient condition for deadlock-free operation, this paper proposes a new control policy such that it can avoid deadlock completely, and reduce starvation and blocking situations significantly. It attempts to release an appropriate number of jobs into the system and control the order of resource usage based on the state information in the net model. The theoretical results for the correctness of this policy are presented. An AMS allowing routing flexibility and varying operation times is used to demonstrate the potential of the proposed policy